2011
DOI: 10.1002/clc.20857
|View full text |Cite
|
Sign up to set email alerts
|

Rhythm Control for Management of Patients With Atrial Fibrillation: Balancing the Use of Antiarrhythmic Drugs and Catheter Ablation

Abstract: Antiarrhythmic drug (AAD) therapy may be beneficial for patients with symptoms attributable to atrial fibrillation despite adequate rate control. The limited long-term efficacy of AAD and the relatively large proportion of patients discontinuing therapy because of side effects led to the development of nonpharmacological therapies to achieve rhythm control. Pressing questions remain about the effect of ablation therapy on long-term patient outcomes. Based on recent clinical trials and meta-analyses, ablation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
0
4
0
1
Order By: Relevance
“…It is not easy to compare the clinical benefits between AADs and catheter ablation because multiple aspects, such as symptoms, prognosis, safety, and cost effectiveness, are involved in the evaluation of their merits [2]. Practically, it is rational to consider that pharmacological and non‐pharmacological treatments work in a cooperative manner to abolish AF or reduce the incidence and duration of arrhythmic events [3,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not easy to compare the clinical benefits between AADs and catheter ablation because multiple aspects, such as symptoms, prognosis, safety, and cost effectiveness, are involved in the evaluation of their merits [2]. Practically, it is rational to consider that pharmacological and non‐pharmacological treatments work in a cooperative manner to abolish AF or reduce the incidence and duration of arrhythmic events [3,7].…”
Section: Discussionmentioning
confidence: 99%
“…Although some clinical studies have reported that AF ablation is a better choice than antiarrhythmic drug (AAD) therapy for the maintenance of sinus rhythm, AADs are often prescribed empirically to prevent AF recurrence or to alleviate the AF burden even after catheter ablation [2–5]. In this report, we focus on the use of AADs before and after AF ablation.…”
Section: Introductionmentioning
confidence: 99%
“…24, 25 However, further randomized data are needed to determine any impact of catheter ablation on subsequent stroke risk and the durability of any effect. 26 …”
Section: Gaps Of Knowledge In Clinical Thrombosismentioning
confidence: 99%
“…This can largely be attributed to the poor efficacy and harmful side effects of antiarrhythmic drugs (AADs) 9. AAD therapy carries the risk of proarrhythmia and sudden cardiac death,10 while amiodarone can cause thyroid and liver dysfunction, pneumonitis, corneal deposits and skin pigmentation.…”
Section: Rate or Rhythm Control?mentioning
confidence: 99%